2012
DOI: 10.2174/156652412802480844
|View full text |Cite
|
Sign up to set email alerts
|

p53 is an Important Regulator of CCL2 Gene Expression

Abstract: The p53 protein is a sequence-specific DNA-binding factor that regulates inflammatory genes such as CCL2/MCP-1 that may play a role in various diseases. A recent study has indicated that the knockdown of human p53 leads to a strong negative regulation of CCL2 induction. We are therefore interested in how p53 regulates CCL2 gene expression. In the following study, our findings indicate that UV-induced p53 accumulation in mouse macrophages significantly decreases LPS-induced CCL2 production, and that p53 binds t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 70 publications
5
22
0
Order By: Relevance
“…However, it was found that p53 mutants lacking the C-terminal still bound to DNA and maintained significant transactivation and growth suppressor activity [38, 39]. Consistent with these studies, we reported a similar result: without its C-terminal, a short peptide of p53 alone is able to suppress the CCL2 gene expression via its binding activity [20]. …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, it was found that p53 mutants lacking the C-terminal still bound to DNA and maintained significant transactivation and growth suppressor activity [38, 39]. Consistent with these studies, we reported a similar result: without its C-terminal, a short peptide of p53 alone is able to suppress the CCL2 gene expression via its binding activity [20]. …”
Section: Discussionsupporting
confidence: 84%
“…Additionally, a recent study has indicated that the knockdown of p53 leads to a strong negative regulation of CCL2 induction [20]. Therefore, we are interested in a model to test how p53 suppresses CCL2-mediated cancer disease.…”
Section: Introductionmentioning
confidence: 99%
“…These data suggested a non-redundant role for p53-induced CCL2 expression in recruiting NK cells into senescent tumors in vivo. Published chromatin immunoprecipitation experiments show a direct association of p53 with the Ccl2 gene regulatory sequences consistent with the possibility that p53 directly transactivates Ccl2 (Hacke et al, 2010; Tang et al, 2012). Our new results suggested that induction of CCL2 production by p53 is a necessary event leading to the elimination of the senescent tumors by NK cells that recognize NKG2D ligands on the tumor cell surface (Figure 2).…”
Section: The Link Between Intrinsic Tumor Suppression Mechanisms Andsupporting
confidence: 67%
“…Although mounting evidence suggests that the MCP-1/CCR2 axis is involved in fibrosis induced by SiO 2 , a recent study indicated that MCP-1 may exert an anti-fibrotic effect in a CCR2-independent manner (Kalderen et al, 2014). However, the concentration of MCP-1 that was exogenously administered in this study (1-60 nM, or 8.7-522 ng/mL) is much higher than that in most physiological and pathological conditions (0.005-1 ng/mL) (Zickus et al, 1998;Liao et al, 2010;Tang et al, 2012). In the current study, we observed that the level of MCP-1 released by fibroblasts was much lower than the dosage of MCP-1 that was exogenously administered.…”
Section: Discussionmentioning
confidence: 57%